Answer:
The expression that could be used is (-4)(3) + (-4)(
) ⇒ B
Explanation:
Let us revise the distributive property:
The product of a number and the sum of 2 other numbers equal to the sum of the products of the number with the other 2 numbers
We will use this rule to solve the question
∵ The product of -4 and 3
= -4 × 3
→ We can right 3
as (3 +
)
∵ 3
= (3 +
)
∴ -4 × 3
= -4(3 +
)
→ By using the rule above
∵ -4(3 +
) = (-4)(3) + (-4)(
)
∴ -4 × 3
= (-4)(3) + (-4)(
)
∴ The expression that could be used is (-4)(3) + (-4)(
)